PEMANFAATAN DATABASE KEPENDUDUKAN TERDISTRIBUSI PADA RAGAM APLIKASI SISTEM INFORMASI DI PEMERINTAH KABUPATEN/KOTA - Edhy Sutanta; Ahmad Ashari (STMIK PONTIANAK, 2012)
Abstract : Government of Indonesia in this regard Kemendagri is currently implementing an e-ID card (e-KTP) program that was developed by the Single Identification Number (SIN). The program is expected to generate an accurate database of the national population. Availability of better population database will provide the maximum benefit if it can be utilized in various applications of information systems at the regency. Distributed database population is a potential development of e-Gov better, through the development of various primary and secondary/derivative information systems with integrated of database, middleware, and applications which developed by web service technologies. Evaluation of system performance continuously also need to be done as part of the process in the life cycle of information systems. Keywords: e-Government, e-KTP, integration, population database, web service